Education Policy and Black Teachers: Perspectives on Race, Policy, and Teacher Diversity. (September 2020) - White, Terrenda; Woodward, Brian; Graham, DaVonna; Milner, H. Richard; Howard, Tyrone C.
This article examines interview responses from prominent education researchers who were asked to consider the role of major educational policies in the underrepresentation of Black teachers in public schools. Participants considered policies related to accountability and market reforms including testing, school choice and charter schools, and alternative teacher education. Although participants agreed that Black teachers contribute greatly to academic achievement for students, their views differed about whether or how policies undermine the presence of Black teachers in schools. We offer conceptual distinctions between participants' views, including those who described policy as having a mixed impact on Black teachers, those who described policy as having an unintended but harmful impact, and those who described policy as playing a tacit role in systemic marginalization of Black teachers and as a form of institutional racism. We find benefit in all participants' views and offer suggestions for initiatives that seek to strengthen workforce diversity.